Design and fabrication of an automotive frame model leveraging anisotropic topology optimization and tailored fiber placement - Yoshihiro IWANO; Atsushi WADA; Ryohei TAKAYAMA; Masaaki TANAKA; Yuqing ZHOU; Isao OHASHI; Katsuharu YOSHIKAWA; Atsushi KAWAMOTO; Tsuyoshi NOMURA (Mechanical Engineering Journal, 2024)
This paper presents a case study of the design, fabrication, and evaluation of an automotive rear-frame model made of variable axial composites (VAC), using a tailored fiber placement (TFP) technique. Conventionally, the design of a three-dimensional complex VAC structure places significant demands on mechanical engineering expertise (for anisotropic structural design) and on man-hours (for fiber-path CAD). The proposed methods facilitate the design of complex VAC structures with significantly reduced manpower requirements. A computational design method, anisotropic topology optimization, was used to create the base design. The fiber paths on the preform surfaces were generated using a Turing pattern algorithm (based on optimized fiber orientation distributions) subsequent to designing developable three-dimensional surfaces to fill the interior of the target structure. The preforms were fabricated using a computer numerical control (CNC) embroidery machine by stitching the raw fiber tow onto the base fabric in accordance with the generated fiber path data. After stacking the preforms in the mold, they were formed using vacuum-assisted resin-transfer molding (VaRTM). The static stiffness of the prototype was evaluated experimentally, and the results were compared with numerical simulations. This study demonstrates the potential for achieving further weight reduction in large-scale 3D structures by combining innovative computational design techniques with advanced fabrication methods.